Concomitant ablation for non-paroxysmal atrial fibrillation: combined energy versus cryoablation alone - Tsaroev, Bashir; Sharifulin, Ravil; Afanasyev, Alexander; Khrushchev, Sergey; Murtazaliev, Murtazali; Lovtsova, Darya; Kashapov, Robert; Ruzankin, Pavel; Mustaev, Muslim; Bogachev-Prokophiev, Alexander (Frontiers in Cardiovascular Medicine, 2024)
Surgical ablation of atrial fibrillation has been the most efficient treatment for atrial fibrillation (AF). Combined energy (CE) ablation and cryoablation alone (CA) are the most common energy modes used for ablation, however, comparative data is lacking. lower cumulative incidence of stroke (SHR=0.38, 95% CI 0.15-0.97, p=0.043). No significant difference in permanent pacemaker implantation was observed between the two groups.In the setting of concomitant biatrial ablation for non-paroxysmal AF, combined bipolar radiofrequency and cryoablation appear to be a superior treatment modality compared to cryoablation alone in achieving long-term freedom from atrial arrhythmias, in reducing arrhythmia-related hospital readmissions and ischemic strokes.